Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board Part XIII. Chemical Pulps and Writing and Printing Papers from Trema orientalis, Blume - Bhat, R. V.; Jaspal, Narendra S. (Indian Forester, 1953)
Laboratory experiments on the production of chemical pulps by the sulphate process from the wood of Trema orientalis are described. Pilot plant experiments on the preparation of writing and printing papers from this wood are also included. This investigation has shown that chemical pulps in satisfactory yields can be prepared from this wood and these pulps can be utilized in admixture with about 25-40% of a long-fibred pulp such as bamboo pulp for the production of writing and printing papers. Two samples of paper are appended in this bulletin. One of them is a writing paper made from a stock containing 75% of T. orientalis pulp and 25% of bamboo bleached pulp and the other is a printing paper made from a stock consisting of 60% T. orientalis pulp and 40% of bamboo pulp.